Preparation method and application of high-thermal-conductivity nylon composite material

By applying fused deposition technology in nylon 6, nanocarbon fiber and acid anhydride-modified vinyl copolymer system, high thermal conductivity nylon composite materials are prepared, which solves the problems of insufficient thermal conductivity and mechanical properties in the existing technology and achieves efficient thermal conductivity. Manage performance.

CN119331413APending Publication Date: 2025-01-21XIHUA UNIV
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202411859671.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-17
Publication Date
2025-01-21

AI Technical Summary

Technical Problem

It is difficult for the prior art to obtain nylon thermal conductivity composite materials with high thermal conductivity through physical blending methods, and the production process of the three-dimensional thermal conductivity network is complex, the molecular weight is difficult to control, and the repeatability is poor.

Method used

High thermal conductivity nylon composite materials are prepared using fused deposition (FDM) technology. By mixing nylon 6, nano carbon fiber and acid anhydride modified vinyl copolymer, vacuum drying, extrusion granulation, extrusion drawing and fused deposition processing are performed. Forming composite materials with high thermal conductivity and mechanical properties.

Benefits of technology

Through FDM technology, nylon 6 composite materials exhibit high thermal conductivity and mechanical properties in the orientation direction, which is suitable for highly integrated and high-power electronic devices and provides stronger thermal management performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119331413A_ABST
    Figure CN119331413A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of heat conduction materials, in particular to a preparation method and application of a high-heat-conduction nylon composite material, and the preparation method comprises the following steps: A, uniformly mixing nylon 6, carbon nanofibers and an anhydride modified vinyl copolymer, and carrying out vacuum drying to obtain a mixture; and B, carrying out extrusion granulation and extrusion wire drawing on the mixture obtained in the step A, and carrying out fused deposition to obtain the high-thermal-conductivity nylon composite material, according to the method disclosed by the invention, the anhydride modified vinyl copolymer is introduced into a nylon 6 / nano carbon fiber composite material system, so that the nylon 6 / nano carbon fiber / elastomer composite material obtained by a fused deposition technology has fewer pores and warpage compared with a nylon 6 / nano carbon fiber composite material; and higher out-of-plane heat conduction performance and more excellent mechanical performance are shown.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of thermal conductive materials, and in particular to a preparation method and application of a high thermal conductive nylon composite material. Background Art

[0002] With the advent of the 5G era, a new generation of highly integrated, high-power electronic devices is developing rapidly. However, these electronic devices will accumulate a lot of heat during operation. If the heat cannot be dissipated in time, it will have a serious negative impact on the safety, service life and performance of the electronic equipment. Heat dissipation has become a key factor affecting the efficiency and life of the device, which also puts higher requirements on the comprehensive performance of thermal management materials. An ideal strategy is to combine high thermal conductivity fillers with low-density, easy-to-process polymers to form a polymer-based thermally conductive insulating composite material as a heat sink. The current common preparation method is to use physical blending methods such as melt blending and solution blending, but the random distribution and irregular arrangement of fillers limit the effective heat conduction of polymer thermal conductive composite materials, making the actual thermal conductivity of the composite material far from expectations. Therefore, the uniform dispersion and orientation of the filler are the key to obtaining high thermal conductivity.

[0003] Nylon 6 (nylon) is one of the five major engineering plastics. With its excellent properties such as light weight, high strength, and easy molding and processing, it is an important material for the preparation of commercial equipment such as engines, LEDs, and radiators. It is widely used in 5G communications, electronic packaging, energy transmission and other fields. At present, the preparation methods of nylon thermal conductive composite materials mainly include melt or solution blending, preparation of nylon thermal conductive composite materials with isolation structure, and construction of a three-dimensional thermal conductive network in the nylon matrix. Like other polymer-based thermal conductive composite materials, nylon thermal conductive composite materials obtained by physical blending often have low thermal conductivity. Although the isolation structure helps to build a thermal conductive path, its mechanical properties are often weak. The three-dimensional thermal conductive network can bring considerable heat transfer capacity to nylon composite materials in both in-plane and out-of-plane directions. However, it is necessary to carry out in-situ polymerization of nylon on the three-dimensional thermal conductive skeleton, which faces problems such as complex process, difficult to control molecular weight, and poor repeatability, making it difficult to produce efficiently. Therefore, being able to obtain nylon composite materials with both high thermal conductivity and mechanical properties through oriented structures is the key to solving the problem.

[0004] As a widely used additive manufacturing technology, fused deposition modeling (FDM) can achieve complex geometric customization and rapid prototyping using polymer-based composite materials. The continued development of FDM technology highlights the importance of FDM-printed polymer-based composites as thermal management materials for a variety of applications including aerospace and biomedical engineering. However, the warping of nylon 6 and the generation of more pores during the printing process limit the improvement of the thermal conductivity of the composite material, which has delayed the development of FDM in the field of nylon-based thermal management materials to a certain extent. Summary of the invention

[0005] In order to solve the above technical problems, an embodiment of the present invention provides a preparation method and application of a high thermal conductivity nylon composite material.

[0006] To achieve the above object, the embodiments of the present invention adopt the following technical solutions: In one aspect, the present invention provides a method for preparing a high thermal conductivity nylon composite material, comprising the following steps: A. mixing nylon 6, carbon nanofiber and anhydride-modified vinyl copolymer, and vacuum drying to obtain a mixture; B. The mixture obtained in step A is subjected to extrusion granulation, extrusion drawing, and then melt deposition to obtain a high thermal conductivity nylon composite material.

[0007] In some embodiments, in step A, based on the percentage of the total weight of the raw materials, the anhydride-modified vinyl copolymer is 10 wt %, the nano-carbon fiber is 2-10 wt %, and the nylon 6 is 80-88 wt %.

[0008] In some embodiments, in step A, the nano carbon fiber has a diameter of 150-200 nm and a length of 10-30 μm.

[0009] In some embodiments, in step A, the vacuum drying temperature is 60° C. and the drying time is 10 h.

[0010] In some embodiments, in step B, the extrusion granulation adopts the following steps: The temperatures of the twin-screw extruder from the first zone to the fifth zone were set to 215°C, 235°C, 240°C, 240°C, and 240°C, respectively, with a screw speed of 120 r / min. The pellets were then pelletized using an air compression pelletizer, and the obtained pellets were placed in a 60°C vacuum drying oven and dried for 10 h, cooled to room temperature, and set aside.

[0011] In some embodiments, in step B, the extrusion drawing process adopts the following steps: Using a single screw extruder, the temperatures from the first zone to the fifth zone were set to 220°C, 240°C, 240°C, 240°C, and 230°C, respectively, with a screw speed of 80 r / min. The wire was drawn through a rolling wire winding machine, then dried and cooled to room temperature for use.

[0012] In some embodiments, the diameter of the wire obtained by drawing the wire through the rolling wire winding machine is controlled to be 1.5 mm to 2 mm.

[0013] In some embodiments, the drying temperature is 60° C. and the drying time is 10 h.

[0014] In some embodiments, in step B, the fused deposition method adopts the following steps: The spare filament was processed by a 3D printer. Before printing, the nozzle temperature of the 3D printer was set to 245 °C, the base temperature was set to 150 °C, the printing speed was set to 400 mm / min, the layer height was set to 0.3 mm, and the filling routing angle was set to 180°.

[0015] On the other hand, the present invention also provides an application of the high thermal conductivity nylon composite material prepared by the above preparation method in heat dissipation of electronic devices.

[0016] Compared with the prior art, the present invention has the following beneficial effects: In the method of the present invention, an anhydride-modified vinyl copolymer (elastomer) is introduced into the nylon 6 / nanocarbon fiber composite material system, so that the nylon 6 / nanocarbon fiber / elastomer composite material obtained by the fused deposition technology has fewer pores and warpages than the nylon 6 / nanocarbon fiber composite material, and exhibits higher out-of-plane thermal conductivity and better mechanical properties. The nozzle shear force of FDM can make the nylon 6 molecular chain and the one-dimensional thermal conductive filler obtain an oriented structure in the printing direction. This structure can bring considerable thermal conductivity and mechanical properties to the nylon 6 composite material in the orientation direction. The nylon 6 composite material obtained by fused deposition (FDM) brings a thermal management material with stronger comprehensive performance to highly integrated and high-power electronic devices, and has broad application prospects in the field of electronic thermal management industry. BRIEF DESCRIPTION OF THE DRAWINGS

[0017] Figure 1 Figure a is the cross-sectional brittle fracture SEM image of the 5wt% CNFs-AEC sample; Figures b, d, and c are the continuous enlarged images of Figure a, respectively; Figure 2Figure a is the DSC curves of 10wt% CNFs and 10wt% CNFs-AEC samples; Figure b is an optical photograph of the side of the 10wt% CNFs-AEC rectangular sample; Figure c is an optical photograph of the side of the 10wt% CNFs rectangular sample; Figure 3 Figure a shows the in-plane thermal conductivity and out-of-plane thermal conductivity of nylon-AEC, 2wt% CNFs-AEC, 5wt% CNFs-AEC and 10wt% CNFs-AEC samples; Figure b shows the in-plane and out-of-plane thermal conductivity of 10wt% CNFs and 10wt% CNFs-AEC samples; Figure c shows the surface optical photograph of the 10wt% CNFs-AEC sample; Figure d shows the surface optical photograph of the 10wt% CNFs sample; Figure 4 Figure a is the tensile stress-strain curves of the composite materials of 5wt% CNFs-AEC, 10wt% CNFs-AEC and 10wt% CNFs; Figure b is the statistical graph of the tensile strength test results; Figure c is the statistical graph of the elongation at break test results; Figure d is the optical photograph of the composite material of 5wt% CNFs-AEC during the tensile test; Figure 5 Figure a is the cross-sectional brittle fracture SEM image of the 5wt% CNFs-AEC-C sample; Figure b is the cross-sectional brittle fracture SEM image of the 5wt% CNFs-AEC sample; Figure 6 Figure a shows the out-of-plane thermal conductivity of nylon-AEC, nylon-AEC-C, 2wt%CNFs-AEC, 2wt%CNFs-AEC-C, 5wt%CNFs-AEC, 5wt%CNFs-AEC-C, 10wt%CNFs-AEC, and 10wt%CNFs-AEC-C samples; Figure b shows the out-of-plane thermal conductivity of 10wt%CNFs, 10wt%CNFs-AEC, 10wt%CNFs-C, and 10wt%CNFs-AEC-C samples; Figure 7 Figure a is the tensile stress-strain curves of 5wt% CNFs-AEC-C, 10wt% CNFs-AEC-C, and 10wt% CNFs-C samples; Figure b is a statistical chart of the tensile strength test results; and Figure c is a statistical chart of the elongation at break test results. DETAILED DESCRIPTION

[0018] The following will be combined with the accompanying drawings to clearly and completely describe the technical solutions in some embodiments of the present disclosure. Obviously, the described embodiments are only part of the embodiments of the present disclosure, rather than all the embodiments. Based on the embodiments provided by the present disclosure, all other embodiments obtained by ordinary technicians in this field belong to the scope of protection of the present disclosure.

[0019] 1. Materials Table 1 name Abbreviation model form source Nylon 6 Nylon 73G15L Particles DuPont Carbon Nanofiber CNFs CNT905 Diameter 150~200 nm Length 10~30 μm Beijing Deke Island Gold Elastomer (anhydride modified vinyl copolymer) AEC N493 Particles DuPont 2. Experimental part (1) Mixing Configuration of mixed masterbatch: Mix nylon, CNFs and AEC according to the proportions in Table 2, shake well and put into a 60°C vacuum drying oven for drying for 10 h. After turning off the oven, cool to room temperature and store dry, then take out for later use.

[0020] (2) Extrusion granulation The mixed masterbatch was extruded and pelletized using a twin-screw extruder and an air-compressed pelletizer, i.e., the temperature of the twin-screw extruder from the first zone to the fifth zone (feeding end to discharging end) was 215°C, 235°C, 240°C, 240°C, 240°C, the screw speed was 120 r / min, and the wire pulling and pelletizing speed matched the extrusion speed. The pellets obtained by pelletizing with the air-compressed pelletizer were placed in a 60°C vacuum drying oven and dried for 10 h. After the vacuum drying oven was closed, they were cooled to room temperature and dried for storage, and then taken out for use.

[0021] (3) Extrusion drawing The prepared pellets were extruded into wires using a single-screw extruder, a laser diameter gauge and a rolling wire winder. The temperatures of the single-screw extruder from the first zone to the fifth zone (feeding end to discharging end) were 220°C, 240°C, 240°C, 240°C, and 230°C, and the screw speed was 80 r / min. Under the calibration of the laser diameter gauge, the diameter of the wire was adjusted by changing the speed of the rolling wire winder to ensure that it was 1.75 mm ± 0.25 mm. The obtained wire was placed in a 60°C vacuum drying oven and dried for 10 h. After turning off the oven, it was cooled to room temperature and dried for storage, and then taken out for later use.

[0022] (4) Fused Deposition Modeling (FDM) The prepared filaments were processed using a 3D printer to print out rectangular and dumbbell-shaped samples for subsequent thermal conductivity and mechanical properties tests. Before printing, the nozzle temperature was set to 245 °C, the base temperature was set to 150 °C, the printing speed was set to 400 mm / min, the layer height was set to 0.3 mm, and the fill trace angle was set to 180 °. After printing, the obtained samples were placed in a drying oven as the final nylon 6 composite material for storage.

[0023] The operation steps of each embodiment are as in the experimental part above, and the specific raw material components are shown in Table 2 below Table 2 Case Sample name AEC content (wt%) CNFs content (wt%) Nylon 6 content (wt%) Comparative Example 1 nylon-AEC 10 0 90 Example 1 2wt%CNFs-AEC 10 2 88 Example 2 5wt%CNFs-AEC 10 5 85 Example 3 10wt%CNFs-AEC 10 10 80 Comparative Example 2 10wt%CNFs 0 10 90 3. Characterization The microscopic morphology of the above samples was analyzed by scanning electron microscopy (SEM, JSM-IT800, Jieoulu Science and Trade Co., Ltd., Beijing). The 5wt% CNFs-AEC sample (i.e., the nylon 6 composite material obtained in Example 2) after printing was placed in liquid nitrogen for 10 min and then brittle fractured, and the brittle fracture surface was selected as the observation object. The tensile strength and elongation at break of the printed samples (dumbbell shape) with different CNFs contents were characterized by an electronic universal testing machine (E44 104, Meters Industrial Systems Co., Ltd., USA), and the stress-strain curve was plotted. The tensile speed was set to 5 mm / min before the test. The thermal behavior of 10wt% CNFs (Comparative Example 2) and 10wt% CNFs-AEC (Example 3) samples was analyzed using a differential thermal analyzer (DSC, TA25, TA Instruments, USA) under a nitrogen atmosphere. In the program, the temperature rise and fall interval was set to 50 ℃~250 ℃, and the temperature rise and fall rate was 10 ℃ / min. The thermal conductivity of the samples was tested using a thermal constant analyzer (TPS2200, Hot Disk, Sweden) based on the transient plate heat source method, and the test process met the ISO 22007-2 standard.

[0024] 4. Results and Discussion (1) Microscopic morphology Figure 1 Figure a is a cross-sectional brittle fracture SEM image of a 5 wt % CNFs-AEC sample (Example 2), and Figures b, d, and c are successive enlarged images of Figure a. Figure 1 As shown in Figures b and d, CNFs are oriented in the direction of the arrow (printing direction) inside nylon 6 and are evenly dispersed without obvious agglomeration. Figure 1 As shown in Figure c, there is almost no gap between the contact between CNFs and the nylon 6 matrix. This shows that CNFs show good dispersibility and compatibility in the nylon 6-AEC system. In the prior art, CNFs tend to agglomerate in nylon 6, and there are often pores between CNFs and nylon 6. This shows that the introduction of AEC enhances the dispersibility and compatibility of CNFs in nylon 6 during the printing process. In addition, FDM enables CNFs to establish a thermal conduction path along the printing direction inside the composite material. This is positive for enhancing the thermal conductivity of the composite material.

[0025] (2) Thermal behavior analysis The crystal characteristics of 10wt% CNFs (Comparative Example 2) and 10wt% CNFs-AEC (Example 3) samples were characterized by DSC. Figure 2As shown in Figure a, the crystal forms of nylon 6 in the 10wt% CNFs sample are γ-form and α-form (double peak), while the crystal forms in the 10wt% CNFs-AEC sample are all the more stable α-form (single peak), indicating that the introduction of AEC has led to changes in the crystallization of nylon 6.

[0026] The 10wt% CNFs rectangular sample showed obvious warping. Figure 2 The 10wt% CNFs-AEC rectangular sample shown in Figures b and c has almost no warping. This is because the introduction of AEC affects the crystallization of nylon 6, thereby improving the warping of the sample, which has a positive effect on the overall performance of the sample.

[0027] (3) Thermal conductivity The thermal conductivity of the composite material was analyzed by thermal constant analyzer. Figure 3 As shown in Figures a and b, the vertical direction is the out-of-plane heat conduction direction of the composite material (K ⊥ ), the vertical direction is consistent with the printing direction, and the horizontal direction is the in-plane heat conduction direction (K ∥ ), the horizontal direction is perpendicular to the printing direction.

[0028] like Figure 3 In Figure a, the out-of-plane thermal conductivity of the composite material gradually increases with the increase of CNFs content. The out-of-plane thermal conductivity of the 10wt% CNFs-AEC sample reaches 5.3 W / mK, which is 2204% higher than that of the nylon-AEC sample. This is because as the CNFs content increases, the thermal conductivity path formed by CNFs in the nylon 6 along the out-of-plane direction gradually improves, and finally presents a step-by-step increase in thermal conductivity. However, the thermal conductivity of the composite material in the in-plane direction has basically not changed, and is always around 0.23 W / mK. This is because there is no oriented CNFs structure in the out-of-plane direction of the composite material, and a thermal conductivity path cannot be formed.

[0029] In addition, the out-of-plane thermal conductivity changes of 10wt% CNFs and 10wt% CNFs-AEC samples were studied separately ( Figure 3 (b) The out-of-plane thermal conductivity of the 10wt% CNFs-AEC sample is 46% higher than that of the 10wt% CNFs sample (3.7 W / mK). This indicates that the introduction of AEC enhances the out-of-plane thermal conductivity of the composite material. As mentioned earlier, the introduction of AEC improves the warpage of the printed material, which is beneficial to the improvement of the thermal conductivity of the sample. In addition, Figure 3 As shown in Figure c, the surface of the 10wt% CNFs-AEC rectangular sample is smooth and almost pore-free. Figure 3As shown in Figure d, many pores appear on the surface of the 10wt% CNF rectangular sample. This shows that the introduction of AEC reduces or even eliminates the pores in the printed material. In the printing process of nylon 6 composites, the nozzle extrusion volume at the current moment is often affected by uneven filler dispersion or the appearance of bubbles, which makes the sample prone to some discontinuities and holes during the printing process, directly reducing the heat conduction channel at the macro level and reducing the thermal conductivity of the composite material. However, the introduction of AEC optimizes the dispersibility and compatibility of CNFs in nylon 6, enhances the processability of the composite material, reduces the impact of sudden changes in extrusion volume on the printed sample, reduces the appearance of pores, ensures the continuity of the melt, and increases the heat conduction channel in the out-of-plane direction of the sample, thereby enhancing the out-of-plane thermal conductivity of the composite material. In summary, the introduction of AEC enhances the thermal conductivity of the composite material and expands the advantages of FDM in the field of nylon-based thermal management materials.

[0030] (4) Mechanical properties The tensile properties of 5wt%CNFs-AEC, 10wt%CNFs-AEC and 10wt%CNFs dumbbell-shaped samples were characterized by tensile tests. Figure 4 In Figure a, the original stress-strain curve of the sample was obtained and the tensile strength of the sample was extracted from it (such as Figure 4 b) and elongation at break ( Figure 4 With the increase of CNFs content, the tensile strength of the composite material decreased slightly, from 50.72 MPa (5wt% CNFs-AEC) to 46.29 MPa (10wt% CNFs-AEC) ( Figure 4 (Figure b in the figure), this is because more CNFs means more interfaces between CNFs and the nylon matrix, which are more likely to form defects during the stretching process, thereby reducing the strength. In addition, the tensile strength of the composite material with 10wt% CNFs is only 28.59 MPa, indicating that AEC enhances the tensile strength of the composite material (increased by 62%). The introduction of AEC not only increases the dispersibility and compatibility of CNFs in nylon 6, but also reduces the porosity of the printed samples and improves the warping, ultimately leading to an increase in the strength of the composite material. For the elongation at break of the composite material, the 5wt% CNFs-AEC sample reached 181.3% ( Figure 4 Figure d in the figure records the state of extreme elongation during the stretching process). Although the elongation at break of the 10wt% CNFs-AEC sample decreased, it still remained at 90.4% ( Figure 4(c in Figure 1). The elongation at break of the 10wt% CNFs sample is 73%, which is lower than that of the 10wt% CNFs-AEC sample, indicating that AEC enhances the elongation at break of the composite material (increased by 24%). Nylon 6 molecular chains and CNFs are highly oriented due to shear force induction during the 3D printing process. These oriented structures bring excellent mechanical properties to the composite material in the orientation direction, and the introduction of AEC further enhances these mechanical properties, bringing broad application prospects for 3D printing nylon-based composite materials.

[0031] 5. Comparative experiment between FDM and CM Material: The materials are the same as above.

[0032] Experimental steps: (1) Preparation of mixed masterbatch: Nylon, CNFs and AEC were mixed according to the proportions in Table 3, shaken evenly and placed in a 60°C vacuum drying oven for drying for 10 h. After turning off the oven, the mixture was cooled to room temperature and dried for storage. The mixture was then taken out for later use.

[0033] Table 3 Sample name AEC content (wt%) CNFs content (wt%) Nylon 6 content (wt%) nylon-AEC-C 10 0 90 2wt%CNFs-AEC-C 10 2 88 5wt%CNFs-AEC-C 10 5 85 10wt%CNFs-AEC-C 10 10 80 10wt%CNFs-C 0 10 90 (2) Extrusion granulation The mixed masterbatch was extruded and pelletized using a twin-screw extruder and an air-compressed pelletizer, i.e., the temperature of the twin-screw extruder from the first zone to the fifth zone (feeding end to discharging end) was 215°C, 235°C, 240°C, 240°C, 240°C, the screw speed was 120 r / min, and the wire pulling and pelletizing speed matched the extrusion speed. The pellets obtained by pelletizing with the air-compressed pelletizer were placed in a 60°C vacuum drying oven and dried for 10 h. After the vacuum drying oven was closed, they were cooled to room temperature and dried for storage, and then taken out for use.

[0034] (3) Compression molding (CM) The prepared pellets were compression molded using a flat vulcanizer. First, preheat at 245 °C and 0 MPa for 5 min, then vulcanize at 245 °C and 10 MPa for 5 min, and finally cold press at 10 °C and 10 MPa for 5 min. Multiple exhausts were set before vulcanization to remove the air inside the mold to ensure the quality of the final sample. After compression molding, the obtained samples were placed in a drying oven for storage.

[0035] Characterization: The microscopic morphology of the sample was analyzed by scanning electron microscopy (SEM, JSM-IT800, Jieoulu Science and Technology Co., Ltd., Beijing). The 5wt% CNFs-AEC sample (Example 2) after printing was placed in liquid nitrogen and frozen for 10 minutes before brittle fracture, and the brittle fracture surface was selected as the observation object. The tensile strength and elongation at break of the printed samples (dumbbell shape) with different CNFs contents were characterized by an electronic universal testing machine (E44 104, Meters Industrial Systems, Inc., USA), and the stress-strain curve was plotted. The stretching speed was set to 5 mm / min before stretching. The thermal conductivity of the sample was tested using a thermal constant analyzer (TPS2200, Hot Disk, Sweden) based on the transient flat plate heat source method, and the test process met the ISO 22007-2 standard.

[0036] Results and Discussion: (1) Microscopic morphology: Figure 5 Figure a and Figure 5 Figure b shows the cross-sectional brittle fracture SEM images of the 5wt% CNFs-AEC-C sample and the 5wt% CNFs-AEC sample. For the 5wt% CNFs-AEC sample, the CNFs exhibited a distinct oriented structure. On the contrary, for the 5wt% CNFs-AEC-C sample, the CNFs exhibited a randomly arranged disordered structure. These randomly arranged CNFs are difficult to form a thermal conductive path inside the composite material, which will greatly limit the improvement of the thermal conductivity of the composite material.

[0037] (2) Thermal conductivity Figure 6 Figure a shows the thermal conductivity of each sample under two different processes. The thermal conductivity of the sample obtained by FDM gradually increases with the increase of CNFs content. This part has been explained in the previous experiment. Here we focus on the difference in the influence of FDM and CM on the thermal conductivity of the sample under the same composition. For CM, increasing the CNFs content has very limited effect on the improvement of the thermal conductivity of the sample. Even the thermal conductivity of the highest 10wt% CNFs-AEC-C sample is only 0.411 W / mK.

[0038] This is also explained in the previous SEM content. CM did not induce orientation of CNFs, resulting in random arrangement of CNFs inside the composite material, and unable to form a heat conduction path. The thermal conductivity of the 10wt% CNFs-AEC sample is 1193% higher than that of the 10wt% CNFs-AEC-C sample ( Figure 6 (a in the figure).

[0039] Figure 6Figure b in the figure expresses the selectivity of the process for the behavior of introducing AEC into the system to enhance the thermal conductivity of the composite material. The thermal conductivity of the 10wt% CNFs-AEC sample is 46% higher than that of the 10wt% CNFs sample, which has been explained in the previous content. However, the thermal conductivity of the 10wt% CNFs-AEC-C sample is 35% lower than that of the 10wt% CNFs-C sample. In other words, when the process is ordinary blending such as CM, the introduction of AEC not only fails to enhance but reduces the thermal conductivity of the composite material. This is because when CNFs do not form a thermal conduction path inside the composite material, the thermal conductivity of the material is mainly affected by the CNFs-nylon interface thermal resistance. After the introduction of AEC with lower intrinsic thermal conductivity, more interface thermal resistance appears, namely CNFs-AEC and AEC-nylon, thereby reducing the thermal conductivity of the composite material.

[0040] On the contrary, when the processing method is FDM, since the CNFs heat conduction path is formed inside the composite material, the thermal conductivity of the composite material is mainly determined by the CNFs-CNFs interface thermal resistance. Therefore, the introduction of AEC will not reduce the thermal conductivity of the composite material, but will increase the thermal conductivity of the composite material because of the enhanced dispersion of CNFs in the system, reduced porosity of the printed sample, improved warping, etc. In short, the introduction of AEC to enhance the thermal conductivity of the composite material is specific to FDM.

[0041] (3) Mechanical properties Figure 7 Figures a, b, and c are the tensile stress-strain curves, tensile strength, and elongation at break of 5wt% CNFs-AEC-C, 10wt% CNFs-AEC-C, and 10wt% CNFs-C samples. For the nylon-CNFs samples obtained by CM, although the introduction of AEC increased the elongation at break of the composite material (increased by 36%), it slightly reduced the tensile strength of the composite material (reduced by 7%), which is consistent with the influence of elastomers on the mechanical properties of nylon composites under ordinary blending processes. Combined with previous experiments, it can be concluded that the introduction of AEC to increase the strength of nylon-CNFs composites is also specific to the FDM process.

[0042] In summary, the fused deposition modeling (FDM) process (oriented arrangement of thermal conductive fillers, customized thermal conductive direction) has advantages over ordinary blending (random arrangement of thermal conductive fillers) in enhancing the thermal conductivity of nylon-based thermal management materials. Introducing AEC into the nylon / CNFs system can enhance the thermal conductivity and tensile strength of the composite material. This mechanism is only applicable to FDM, not to hot compression molding, and is specific to FDM.

[0043] In the description of this specification, specific features, structures, materials or characteristics may be combined in an appropriate manner in any one or more embodiments or examples.

[0044] The above is only a specific embodiment of the present invention, but the protection scope of the present invention is not limited thereto. Any person skilled in the art can easily think of changes or substitutions within the technical scope disclosed by the present invention, which should be included in the protection scope of the present invention. Therefore, the protection scope of the present invention should be based on the protection scope of the claims.

Claims

1. A method for preparing a high thermal conductivity nylon composite material, characterized in that: The following steps are involved: A. mixing nylon 6, carbon nanofiber and anhydride-modified vinyl copolymer, and vacuum drying to obtain a mixture; B. The mixture obtained in step A is subjected to extrusion granulation, extrusion drawing, and then melt deposition to obtain a high thermal conductivity nylon composite material.

2. The preparation method according to claim 1, characterized in that: In step A, based on the percentage of the total weight of the raw materials, the anhydride-modified vinyl copolymer is 10 wt %, the nano-carbon fiber is 2-10 wt %, and the nylon 6 is 80-88 wt %.

3. The preparation method according to claim 1, characterized in that: In step A, the nano carbon fiber has a diameter of 150-200 nm and a length of 10-30 μm.

4. The preparation method according to claim 1, characterized in that: In step A, the vacuum drying temperature is 60° C. and the drying time is 10 h.

5. The preparation method according to claim 1, characterized in that: In step B, the extrusion granulation adopts the following steps: The temperatures of the twin-screw extruder from the first zone to the fifth zone were set to 215°C, 235°C, 240°C, 240°C, and 240°C, respectively, with a screw speed of 120 r / min. The pellets were then pelletized using an air compression pelletizer, and the obtained pellets were placed in a 60°C vacuum drying oven and dried for 10 h, cooled to room temperature, and set aside.

6. The preparation method according to claim 1, characterized in that: In step B, the extrusion drawing adopts the following steps: Using a single screw extruder, the temperatures from the first zone to the fifth zone were set to 220°C, 240°C, 240°C, 240°C, and 230°C, respectively, with a screw speed of 80 r / min. The wire was drawn through a rolling wire winding machine, then dried and cooled to room temperature for use.

7. The preparation method according to claim 6, characterized in that: The diameter of the wire obtained by drawing the wire through the rolling wire winding machine is controlled to be 1.5 mm to 2 mm.

8. The preparation method according to claim 6, characterized in that: The drying temperature is 60° C. and the drying time is 10 h.

9. The preparation method according to claim 1, characterized in that: In step B, the fused deposition method adopts the following steps: The spare filament was processed by a 3D printer. Before printing, the nozzle temperature of the 3D printer was set to 245°C, the base temperature was set to 150°C, the printing speed was set to 400 mm / min, the layer height was set to 0.3 mm, and the filling routing angle was set to 180°.

10. Use of the high thermal conductivity nylon composite material prepared by the preparation method according to any one of claims 1 to 9 in heat dissipation of electronic devices.

Citation Information

Patent Citations

  • Modified nylon material for 3D printing applied to FDM (fused deposition molding) technology and printing method of modified nylon material

    CN105778484A

  • Insulating and heat-conducting modified nylon 6 composite material

    CN109880355A

  • Manufacturing method for 3D printing workpiece with high interfacial heat conductivity

    CN111823573A

  • Preparation method of recyclable wear-resistant high-thermal-conductivity nylon 66 composite material

    CN112646370A

  • High-thermal-conductivity Ti3C2Tx / graphene microchip / polylactic acid electromagnetic shielding composite material and 3D printing preparation method thereof

    CN113059870A